2020
DOI: 10.1186/s40337-020-00349-6
|View full text |Cite
|
Sign up to set email alerts
|

The outcome at follow-up after inpatient eating disorder treatment: a naturalistic study

Abstract: Background Patients with eating disorders may experience a severe and enduring course of illness. Treatment outcome for patients provided with inpatient treatment is reported as poor. Research to date has not provided consistent results for predictors of treatment outcome. The aims of the study were to investigate rates of remission at follow-up after inpatient treatment, symptom change from admission to follow-up, and predictors of treatment outcome. Methods The follow-up sample consisted of 150 female adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Intake of dietary iron was not significantly different between amenorrhoeic and eumenorrhoeic subjects, nor between subjects and healthy controls at 3-year follow-up. 4 This prospective 3-year outcome study shows, in accordance with newly published data [9,33], that 50e60% of young individuals with AN can reach full or partial symptom recovery, and that remission is possible also for patients with severe AN who need inpatient treatment. Further, around 40% of individuals have other psychiatric diagnoses, and individuals with early onset of AN have greater difficulty to recover.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Intake of dietary iron was not significantly different between amenorrhoeic and eumenorrhoeic subjects, nor between subjects and healthy controls at 3-year follow-up. 4 This prospective 3-year outcome study shows, in accordance with newly published data [9,33], that 50e60% of young individuals with AN can reach full or partial symptom recovery, and that remission is possible also for patients with severe AN who need inpatient treatment. Further, around 40% of individuals have other psychiatric diagnoses, and individuals with early onset of AN have greater difficulty to recover.…”
Section: Discussionsupporting
confidence: 76%
“…Research regarding dietary intake and food choice in individuals with AN is limited and the high relapse rate suggests that many patients have difficulties to maintain a healthy diet after hospital treatment [8]. Several studies have shown increase in body weight and decrease in eating disorder symptoms (for example anxiety, restraint, eating concern, shape concern and weight concern) at discharge from hospital and that these changes are maintained one year or more [9,10], but these studies lack information about dietary intake and nutritional status. Nova et al [11] examined dietary intake and body composition repeatedly in a group of female adolescents with AN for one year beginning at hospital admission and showed that teenagers returned to restrictive and pathological eating, with low energy intake from fat and carbohydrates as well as low variation in food choices, after hospital discharge [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent 5-year annual follow-up study of adult patients with AN following intensive weight rehabilitation, only 46% maintained a BMI greater than 18.5 throughout follow-up, with only 17% sustaining both a BMI greater than 18.5 and normalization of EDE-Q scores [ 5 ]. These data are consistent with that from several naturalistic studies that have followed outpatients with AN, reporting remission rates from 39 to 42% [ 21 23 ]. One large cohort study of adults with AN has found that 31% were recovered after 9 years and 62% recovered at 22 years [ 24 ].…”
Section: Introductionsupporting
confidence: 90%
“…In fact, in spite of providing patients with specific discharge plans (6), a substantial number of patients require multiple hospitalizations, sometimes over a short period of time. There are few longitudinal studies in AN on inpatients, and RA is rarely considered as an outcome itself, with most works focusing instead on the stabilization/improvement of outcome measures at follow-up (8)(9)(10)(11). Earlier data suggested RAs as becoming increasingly frequent over time (12), but no other data are currently available for adults with AN.…”
Section: Introductionmentioning
confidence: 99%